2018
DOI: 10.1177/1073191118787328
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Parent-Rated Scale for Selective Mutism

Abstract: Assessment of selective mutism (SM) is hampered by the lack of diagnostic measures. The Frankfurt Scale of Selective Mutism was developed for kindergarteners, schoolchildren, and adolescents, including the diagnostic scale (DS) and the severity scale (SS). The objective of this study was to evaluate this novel, parent-rated questionnaire among individuals aged 3 to 18 years ( n = 334) with SM, social phobia, internalizing disorders, and a control group. Item analysis resulted in high item-total correlations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 23 publications
4
38
0
6
Order By: Relevance
“…Our mean score findings in the TDs are quite similar to previous findings from the small group ( n = 18) of referred children diagnosed with anxiety disorders other than SM, where a total SMQ score >2.5 was reported ( Bergman et al, 2008 ). The relatively comparable parent-rated scores between children with anxiety disorders in the Bergman study ( Bergman et al, 2008 ) and the TDs in this study have also been reported on the more recently developed parent-rated FSSM ( Gensthaler et al, 2018 ). In the FSSM study, it was demonstrated that children with social phobia had scores about twice as high as those for the TDs and children with other anxiety disorders, and about half as high as the scores for children with SM, thus adding important information on speaking behavior as reported by parents in this diagnostic group ( Gensthaler et al, 2018 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our mean score findings in the TDs are quite similar to previous findings from the small group ( n = 18) of referred children diagnosed with anxiety disorders other than SM, where a total SMQ score >2.5 was reported ( Bergman et al, 2008 ). The relatively comparable parent-rated scores between children with anxiety disorders in the Bergman study ( Bergman et al, 2008 ) and the TDs in this study have also been reported on the more recently developed parent-rated FSSM ( Gensthaler et al, 2018 ). In the FSSM study, it was demonstrated that children with social phobia had scores about twice as high as those for the TDs and children with other anxiety disorders, and about half as high as the scores for children with SM, thus adding important information on speaking behavior as reported by parents in this diagnostic group ( Gensthaler et al, 2018 ).…”
Section: Discussionsupporting
confidence: 77%
“…Children with SAD may also show speech problems, such as longer speech latency, inappropriate tone or low voice volume, and reduced spontaneous speech ( Beidel et al, 2019 ). Whether speaking behavior differentiates the two conditions has not been evaluated until the recent publication of the Frankfurt Scale of Selective Mutism (FSSM; Gensthaler et al, 2018 ). The parent-rated FSSM is a validated, age-adjusted measure of SM for both research and clinical practice and includes a diagnostic scale (DS) and a severity scale for three age groups (3–18 years).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because a social situation is usually influenced by all three factors an interaction between the three components can be assumed and children are usually confronted with more than one anxiety eliciting stimuli [25]. The three factors were confirmed by a factor analysis of a screening questionnaire [26] although another screening tool has found only one factor on which all items loaded [27]. Empirical data on talking patterns of children with SM are sparse yet, but there are some single research results that indicate proof for the existence of such factors that have an influence on the speaking behavior of children with SM.…”
Section: Introductionmentioning
confidence: 99%
“…Children showing SM in its extreme form (i.e., <1%; Bergman et al, 2002;Karakaya et al, 2008) are usually referred to a clinical facility for treatment because the persistent non-speaking behavior obviously hinders them in performing adequately in school and establishing friendships with other children (Manassis, 2009). It is good to bear in mind, however, that SM is a dimensional phenomenon as there are also young children who are not totally silent in certain social situations, but clearly use less spoken language as they would do in other settings (Gensthaler et al, 2020). This means that SM, just like other psychiatric conditions, is better conceptualized as a continuum rather than as a categorical diagnostic entity, and this justifies that its scientific inquiry should not only be conducted in clinical samples but also in non-clinical populations.…”
Section: Introductionmentioning
confidence: 99%